Analisis Bangunan Balai Pemuda Sebagai Ruang Publik - Ibrahim, Rifky Maulana; Arfianti, Ami (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Balai Pemuda is one of Surabaya's iconic buildings and is recognized as a cultural heritage site. Currently, it has been repurposed as a central public space for artistic and cultural activities, featuring galleries, a library, a multifunctional area, and complemented by common facilities, including a spacious open courtyard. In 2019, Surabaya Mayor Tri Rismaharini transformed the youth center into one of Surabaya's landmarks. With these alterations and the introduction of new facilities, Balai Pemuda is classified as a public space, serving as a hub for social activities where the community can engage, socialize, and appreciate the arts and culture of Surabaya. This public space adopts the concept of a creative and cultural center, incorporating elements that represent art and culture within a centralized creative structure. The objective of this research is to assess the extent to which Balai Pemuda is categorized as a public space. The methodology employed is qualitative descriptive, utilizing library research as the research type. Survey techniques are based on secondary data obtained through the exploration of pertinent academic sources, followed by analysis and conclusions. The results of this research will indicate that Balai Pemuda is indeed a public space that effectively connects to the surrounding area and individuals. It functions as an effective public space based on the concept of a creative and cultural center.